How the special needs brain learns - Sousa, David A. (Thousand Oaks, California Corwin Press, Inc., 2001)
Today's classrooms embrace students of all abilities, and David A. Sousa's latest work provides the most up-to-date information and insights on how to work effectively with each one of them.
How the brain learns -- When brains differ -- Attention disorders -- Speech disabilities -- Reading disabilities -- Writing disabilities -- Mathematical disabilities -- Sleep disorders -- Emotional and behavioral disorders -- Autism -- Putting it all together.
Includes bibliographical references (pages 221-230) and index.
Keywords: Learning disabled children -- Education; Learning; Cognition in children